Developing Organisational Thinking Skills of the Auditor and Its Effect on the Audit Planning - Dheyab, Sanaa Manfi; Wahhab, Asaad (Technium Social Sciences Journal, 2025)
Due to administrative and financial corruption, Iraq’s auditing profession has encountered substantial obstacles for almost two decades. In Iraq, professional accounting and auditing organisations have endeavoured to identify deficiencies in the practices of auditors, both in audit firms and among public auditors. One of the crucial choices made by the Iraqi Auditing and Oversight Profession Council was to mandate the application of international auditing standards for auditors of Iraqi audit firms due to the lack of a local standard. It is essential to highlight that there is no local auditing standard for planning the audit process; therefore, Iraqi auditors utilize the IAS 300. Nonetheless, many concerns about audit failure stem from inadequate preparation and the advent of novel fraudulent practices that auditors cannot detect and appropriately prepare for. As a result, improving the auditor’s competency in various cognitive approaches may aid in creating a high-quality plan by IAS 300. The current study aims to assess the auditor’s organizational thinking and illustrate its influence on the audit planning process. A questionnaire consisting of three axes was prepared to achieve the study objectives. The first axis was allocated to demographic information, and the second axis was assigned to the auditor’s organiational thinking, which includes eight dimensions: analysis and evaluation, risk management, critical thinking, time pressure, strategic thinking, cooperation and communication, creative thinking, and learning and development. Four questions were developed for each of these dimensions. The third axis was allocated to planning the audit process, which contained 14 questions approved by the International Auditing Standard 300. SPSS was used to analyze data, which used factor analysis and half-split to demonstrate the validity and reliability of the questionnaire. In contrast, simple linear regression was used to test the research hypotheses. A correlation of 98.9% was found between organizational thinking and planning the audit process. This percentage varied when measuring each dimension of organizational thinking while planning the audit process. The results also indicated that organizational thinking helps auditors critically analyze and evaluate the organization’s work, seeking to improve its efficiency and effectiveness by examining systems and various processes to identify areas for improvement.